Civilizing natures : race, resources, and modernity in colonial South India - Philip, Kavita, 1964- (Rutgers University Press, 2004)
Annotation "An interdisciplinary exploration of science, nature, and race in colonial India."
Keywords: Science -- India, South -- History -- 19th century.; Science -- Social aspects -- India, South -- History -- 19th century.; Sciences -- Inde (Sud) -- Histoire -- 19e siècle.; Sciences -- Aspect social -- Inde (Sud) -- Histoire -- 19e siècle.; SCIENCE -- History.; Science; Science -- Social aspects; South India; 1800-1899; Andre fag (naturvidenskab og teknik) -- Andre fag; History